Fisheries Landings in the Cabo Verde EEZ 2003-2022 in relation to mean annual Chlorophyll-a and Sea Surface Temperature - Correia, Sandra; da Luz, Alciany; Vieira, Nuno; Correia, Maria Auxilia; Cruz, Iolanda; Ramos, David; da Cruz, Elisia; Medina, Zoraida; Martins, A; Hauss, Helena; Bonnin, Marie; Martinez, Elodie; et al. (PANGAEA, 2025)
These data summarize both commercial and artisanal annual landings (tonnes) of tuna and tuna-like species, small pelagics, and all other groups caught within the exclusive economic zone (EEZ) of Cabo Verde. The original data source are the IMAR annual reports: IMAR 2023 – Estatística das pescas de Cabo Verde. Evolução comparada dos desembarques da pesca artesanal e industrial por grupo de espécies de 1999-2023 da frota nacional que operam na Zona Económica Exclusiva (ZEE) de Cabo Verde. Instituto do Mar (Órgãos Delegados do Instituto Nacional de Estatística). For the same year, satellite based mean annual chlorophyll-a and sea surface temperatue values were extracted in the box 14.5-17°N and 22.5-25-5°W from annual Chl-a and SST products from Aqua-MODIS Level 3, with a spatial resolution of 4 km. Tuna and tuna-like species: Katsuwonus pelamid, Euthynnus alleteratus, Acanthocybium solandri, Thunnus obesus, Xiphias gladius, Coryphaena hippurus, Auxis rochei, Makaira nigricans, Thunnus albacares, Trichiurus lepturus, Makaira nigricans, Auxis sp., Auxis thazard, Istiophorus albicans Small pelagics: Selar crumenophthalmus, Trachinotus ovatus, Spicara melanurus, Selene dorsalis, Sardinella maderensis, Trachinotus goreensis, Sphyraena guachancho, Ablennes hians, Pomatomus saltatrix, Decapterus macarellus, Caranx crysos, Trachurus sp., Decapterus punctatus, Decapterus tabl, Scomber colias, Fodiador acutus, Hemiramphus brasiliensis
Keywords: Cape Verde; eastern tropical Atlantic; small pelagic fish; tuna